Performance enhancement of free convective solar air heater by pin protrusions on the absorber - Gilani, S.E. (Elsevier Ltd, 2017)
This paper is aimed to present enhancing technique of the low performing free convective solar air heaters. In order to increase the efficiency of this process, small sized turbulators have been used on the absorber plate that is breaking the viscous layer/sub-layer of the air flowing over the surface. To conduct the experimental investigation, a special test rig was designed and fabricated to measure the effect of these turbulators. The turbulators used in this project are conical shaped pin protrusions on the surface of the absorber. The test rig was a special type of free convective solar air heater comparing 6 different type of absorber plates at once. The results demonstrated that optimum inclination angle of the absorber plate for Malaysian condition was 45 degrees. Staggered arrangement of conical pins were found to be more effective compared to inline arrangement. A total of 3 different pitch of conical pins (16 mm, 32 mm & 48 mm) and 3 different heights of conical pins (2 mm, 3 mm & 4 mm) were tested all in staggered conical pin arrangement. The results showed that pin pitch of 16 mm increased the Nusselt number the most. The efficiency was increased by up to 26.5 for absorber plate with 16 mm pin pitch as compared to flat smooth plate. The pin height of 4 mm proved to be the best in enhancing the Nusselt number. In addition, a correlation was developed to predict the Nusselt number for conical pin protruded plates of dimensional ranges (16 mm < pin pitch < 48 mm) and (2 mm < pin height < 4 mm) under free convective flow for staggered arrangement. The accuracy of the correlation for the entire experimented range is ±27, and at optimum operating parameters, it is reduced to ±8.0. © 2017 Elsevier Ltd